EFEKTIVITAS MODEL PEMBELAJARAN ARIAS TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS IV SEKOLAH DASAR - Fajar Nur Yasin; Ummu Nihayah (Jurnal Muassis Pendidikan Dasar, 2022)
This research  aims to determine the effectiveness of using the ARIAS model on the motivation and learning outcomes of fourth grade elementary school students. The research conducted in this research is quantitative research. The method used in this study was a quasi-experimental research design with nonequivalent (pretest and posttest) control group design. The research sample consisted of 60 students consisting of 30 students in class IVB as the experimental class and 30 students in class IVC as the control class. Data was collected using a questionnaire sheet to determine learning motivation and a test sheet to determine student learning outcomes. The data analysis used was t-test analysis with a significance level of 5%. The results showed that: (1) there was an effectiveness of the ARIAS model on learning motivation by obtaining a sig 2 tailed value of 0.009<0.05 and tcount 2.822 > ttable 1.671, (2) there was an effectiveness of the ARIAS model on student learning outcomes by obtaining a sig 2 value tailed of 0.018<0.05 and tcount 2.508 > ttable 1.671. Thus, there is the effectiveness of using the ARIAS model on the motivation and learning outcomes of fourth grade elementary school students.